Techno-economic analysis of a refrigerated warehouse equipped with on-shelf phase change material for cold storage under different operating strategies. (1st May 2023) - He, Zhaoyu; Guo, Weimin; Song, Long; Zhang, Peng
Highlights: On-shelf phase change material is used for energy storage for its high flexibility. Operating strategy is formulated based on the time-of-use electricity tariff. Combining cold storage and suitable strategy results in the best performance. Cost and energy savings can reach as much as 34.73% and 11.99%, respectively. More techno-economic benefits are obtained in hot seasons or hot climatic regions. Abstract: Refrigerated warehouse plays an important role in food supply chain while it is also a major energy consumer, which requires energy and cost saving techniques. By performing a series of annual operating simulations of a refrigerated warehouse with an area of 15000 m 2 for frozen meat storage using TRNSYS software, the present study aims at comparatively illustrating the advantages of combining cold storage by on-shelf phase change material and both-temperature-and-price-based operating strategy from the techno-economic perspectives, followed by a parametric study discussing the influences of the volume fraction of phase change material and climatic condition. The results show that employing phase change material for cold storage in the refrigerated warehouse without adopting an appropriate operating strategy may result in a more economic loss. For the refrigerated warehouse in Shanghai integrating phase change material with both-temperature-and-price-based strategy, the operational cost and electricity consumption reductions can reach as much as 34.73% and 11.99%, respectively, which are benefited from the incentive of the time-of-use electricity tariff, high coefficient of performance of the refrigerator working at night and energy storage capability of phase change material. In addition, it is shown that such an integration is capable of achieving more benefits in hotter climatic regions with higher cooling load as the annual cost and energy savings reach 32.30 k$ (22.72%) and 227.45 MW·h (11.28%), respectively, in Guangzhou with subtropical climate, while 23.76 k$ (23.33%) and 161.91 MW·h (10.18%), respectively, in Beijing with temperate climate. These results demonstrate the significant potential of integrating phase change material with both-temperature-and-price-based strategy in the refrigerated warehouse for energy saving and cost reduction.